Introduction to software engineering design : - Fox, Christopher (Addison-Wesley, 2006)
Introduction to Software Engineering Design introduces software design with an emphasis on design practice at an introductory level using object-oriented analysis and design techniques and UML 2.0. This text provides comprehensive coverage of software engineering design with a focus on the processes, principles, and practices used to design software products. Readers will learn to design software using a wealth of pedagogical tools that include chapter objectives and orientation diagrams, a large running case study, end-of-section quizzes, team projects and end-of-chapter exercises.